(untitled) - Anderson, Julie (Boston, 2005)
This freshman textbook introduces the fundamentals of object-oriented programming, the syntax of the Java language, good software engineering principles, and effective testing techniques. The authors (Capitol College) show how to instantiate objects, call methods of classes, design user-defined classes, and build graphical user interfaces.
Keywords: Java (Ngôn ngữ chương trình máy tính),Java (Computer program language)